2017
DOI: 10.1038/s41598-017-13270-x
|View full text |Cite|
|
Sign up to set email alerts
|

Multiple Approaches Detect the Presence of Fungi in Human Breastmilk Samples from Healthy Mothers

Abstract: Human breastmilk contains a variety of bacteria that are transmitted to the infant and have been suggested to contribute to gut microbiota development and immune maturation. However, the characterization of fungal organisms in milk from healthy mothers is currently unknown although their presence has been reported in the infant gut and also in milk from other mammals. Breastmilk samples from healthy lactating mothers (n = 65) within 1 month after birth were analyzed. Fungal presence was assessed by different t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
76
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 62 publications
6
76
2
5
Order By: Relevance
“…At the genus level, Malassezia predominated in all countries, followed by Davidiella. In our previous work reporting the presence of fungi in breast milk, Malassezia also represented the most abundant genus (20). Other genera found in the current study, such as Alternaria, Rhodotorula, Saccharomyces, and Candida, were also found in the previous study.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…At the genus level, Malassezia predominated in all countries, followed by Davidiella. In our previous work reporting the presence of fungi in breast milk, Malassezia also represented the most abundant genus (20). Other genera found in the current study, such as Alternaria, Rhodotorula, Saccharomyces, and Candida, were also found in the previous study.…”
Section: Discussionsupporting
confidence: 82%
“…Breast milk is a continuous source of microbes that are transmitted, together with many nutrients and protective compounds, to the infant gut during a critical period when the key regulatory systems of the body are immature (17,18). Although bacteria inhabiting human breast milk have been extensively studied, the presence of fungi in the fluid had not been assessed until recently, when a diversity of fungal phylotypes in breast milk from healthy Spanish mothers was reported by our group (20). The mycobiome, the fungal fraction of the human microbiome, is present in lower abundances and has been much less explored than the bacterial fraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is very interesting because it may imply that human beings are exposed to Saccharomyces since very early in life. In this paper, the authors discussed that this may be due to skin contamination and also raise the intriguing possibility of an entero-mammary pathway involving an internal route (Boix-Amorós et al, 2017). Saccharomyces has also been detected in human faeces a number of times (Nash et al, 2017), being sometimes the dominant genus representing over half of total relative abundance (Huseyin et al, 2017).…”
Section: Mode Of Action In Vivo Of Saccharomyces In Human Beingsmentioning
confidence: 98%
“…Saccharomyces is an abundant (average 15% of all sequence reads) and prevalent member of the milk mycobiome in healthy mothers (Boix-Amorós et al, 2017). This is very interesting because it may imply that human beings are exposed to Saccharomyces since very early in life.…”
Section: Mode Of Action In Vivo Of Saccharomyces In Human Beingsmentioning
confidence: 99%